Predicting marine tourism intention through information processing: an ability-motivation-opportunity framework - Zhuge, Yan; Jiao, Yang; Tong, Hao; Yu, Jie Joseph (Frontiers in Marine Science, 2025)
IntroductionMarine tourism, as a crucial component of the marine economy, generates employment opportunities in traditional marine industries and contributes to sustainable marine economic development. Understanding the drivers and enablers of individuals' travel in marine tourism is therefore essential.MethodsGrounded in the ability–motivation–opportunity framework, this study examines how tourism information quality influences individuals' travel intention toward marine tourism, while considering the moderating roles of travel motivation and information literacy. To test our study model, we follow a survey research design and rely on 268 participants' data.ResultsOur results show that tourism information quality of marine tourism is positively related to individuals' travel intention toward marine tourism. However, only information skills positively moderate the positive relationship between tourism information quality and individuals' travel intention.DiscussionThese results highlight the importance of tourism information quality in fostering marine tourism travel intention, particularly when individuals possess strong information skills. The findings provide practical implications for social media platforms and prospective tourists. The formulation and implementation of policies in the marine tourism industry can be inspired by our findings as well.